Legionella pneumophila: A Microorganism with a Thousand Faces—From Environmental Complexity to Clinical and Technological Challenges - Teresa Maria Assunta Fasciana (Microorganisms, 2026)
Legionella pneumophila epitomizes the concept of a microorganism with “a thousand faces”, reflecting its extraordinary ecological adaptability, genetic diversity, and multifaceted clinical relevance [...]